2022
DOI: 10.3390/diagnostics12051294
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study of Myocardial Radiomics Feature Properties on Energy-Integrating and Photon-Counting Detector CT

Abstract: The implementation of radiomics-based, quantitative imaging parameters is hampered by a lack of stability and standardization. Photon-counting computed tomography (PCCT), compared to energy-integrating computed tomography (EICT), does rely on a novel detector technology, promising better spatial resolution and contrast-to-noise ratio. However, its effect on radiomics feature properties is unknown. This work investigates this topic in myocardial imaging. In this retrospective, single-center IRB-approved study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…For example, it has been investigated whether PCD-CT might not allow the detection of textural changes in periaortic adipose tissue in relation to the presence of local aortic calcification because of its better spatial resolution and signal-to-noise ratio, and thus possibly provide a biomarker for the development of atherosclerosis. 88 The stability of radiomics features in abdominal VMIs 89 and in the myocardium 90 has been investigated, and it could be shown that some texture alterations of the left ventricular myocardium might be associated with the severity of coronary artery calcification estimated by the Agatston score. 91 We are here only at the beginning of a development whose real potential will become apparent in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been investigated whether PCD-CT might not allow the detection of textural changes in periaortic adipose tissue in relation to the presence of local aortic calcification because of its better spatial resolution and signal-to-noise ratio, and thus possibly provide a biomarker for the development of atherosclerosis. 88 The stability of radiomics features in abdominal VMIs 89 and in the myocardium 90 has been investigated, and it could be shown that some texture alterations of the left ventricular myocardium might be associated with the severity of coronary artery calcification estimated by the Agatston score. 91 We are here only at the beginning of a development whose real potential will become apparent in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the distortion of features by beam-hardening artifacts can be excluded in radiomics texture maps. The first results showing the influence of PCCT in comparison with energy integrating detector CT on texture analysis of left ventricular myocardium outline comparable results in terms of first-order features, but differences in higher-order features, suggesting the possible impact of improved image quality on texture analysis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…88 When comparing myocardial texture features derived from EID-CT and PCD-CT scans, similar feature properties may be detectable in case of first-order features; however, in higher-order features, significant differences might be observed between the 2 systems. 89 This indicates the need for further research to properly understand the reasons behind the aforementioned results. Texture features derived from the myocardium scanned with PCD-CT (NAEOTOM Alpha) may have an association with the amount of coronary artery calcification described by Ayx et al 90 Some defined myocardial radiomics-based texture features found to be different between patients with and without coronary artery calcification, resulting in more heterogeneous texture features with increasing Agatston score, which could be due to the possible myocardial fibrosis.…”
Section: Current Evidencementioning
confidence: 99%
“…Results of texture analysis can be affected by many factors such as spatial resolution, SNR, slice thickness, and contrast agent enhancement 88 . When comparing myocardial texture features derived from EID-CT and PCD-CT scans, similar feature properties may be detectable in case of first-order features; however, in higher-order features, significant differences might be observed between the 2 systems 89 . This indicates the need for further research to properly understand the reasons behind the aforementioned results.…”
Section: Myocardial Radiomicsmentioning
confidence: 99%